Manajemen Ekonomi Spiritual: Sebuah Upaya Mengkontruksi Peluang Modal Bagi Generasi Muda Hindu - I Nyoman Subrata (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
The management of the spiritual economy in Balinese social life must be constructed with the development of innovation through the creativity of the younger generation of Hindus, namely by building an opportunity market through ritual activities of Hindu religious ceremonies in Bali. This is a major form of capital in improving the standard of living of Balinese people through making offerings, in addition to being a medium for channeling Balinese skills, it also benefits energy and time to increase income for Balinese people. However, the younger generation of Hindus is still patterned by the paradigm of priyayi elitism and bureaucratic elitism. This needs to be corrected for the Hindu young generation in addressing current global issues. Therefore, innovation is needed in increasing business opportunities for income for the people of Bali.